INDIVIDUAL ANATOMICAL VARIABILITY OF THE EXTERNAL SURFACE CONFIGURATION OF THE CRANIAL VAULT BONES IN BRACHYCEPHALICS - Bondarenko , Olga; Boiarchuk , Olena (Collection of scientific papers «ΛΌГOΣ», 2023)
The scientific work is devoted to a comprehensive morphometric study of the individual anatomical variability of the configuration of the surface of the bones of the cranial vault of brachycephalics in relation to the coordinates of planar points on the outer and inner bone plates. The bones of the cranial vault have a different configuration of the outer surface, which is formed by parabolic curves and circles that determine the curvature of the surface of this area of the bone. The number, position, morphometric parameters and the nature of the distribution of planar coordinate points correlate with the shape of the human skull. The proposed method for describing the configuration of the surface of the bones of the cranial vault makes it possible to more accurately reproduce the craniotopography of the cranial vault in the applied aspect.